Optimisation of biomass, lipid and carbohydrate productivities in chlorellavulgaris for biofuel production - Nordin, Norazela; Yusof, Norjan; Md Nadzir, Syafiqah; Kamari, Azlan; Mohd Yusoff, Mohd Zulkhairi (Penerbit Universiti Teknologi Malaysia, 2022)
Synthesis of lipid and carbohydrate in microalgae simultaneously is essential for cost-effective microalgae-based biofuel production. Statistical optimisation approaches of the Plackett–Burman design (PBD) and central composite design (CCD) were applied to optimise the biomass, lipid, and carbohydrate productivities of the C. vulgaris UPSI-JRM01. The results obtained from PBD shown that NO3- concentration, light intensity and NaHCO3 concentration were the significant factors that affecting biomass productivity. Through CCD, optimum biomass, lipid, and carbohydrate productivities were obtained at 401.81 mg/L NO3–, 11238.20 lux light intensity, and 0.30 g/L NaHCO3, achieving the highest biomass productivity of 404.24 mg/L/day, highest lipid productivity of 65.3 mg/L/day, and highest carbohydrate productivity of 165.43 mg/L/day. The major fatty acid methyl esters (FAMEs) produced were palmitic acid (33.54%) and linoleic acid (30.29%), thus producing microalgae-based biodiesel with properties complying with international biodiesel standards.